Evaluating compatibility between machines and operations for aerospace engine products - Costanzo, Roberto; Limbayyaswamimath, Vedanth (My University, 2021)
Purpose - In today’s globalized marketplace, businesses of all kinds experience a constant change in customer needs and demands. For a company to stay competitive, it is essential to have flexible production systems, which allow for rapid production changes and ensure that new products are effectively and quickly introduced into the factory. Before a new product, or a change in product specifications, is introduced into the production system, two main areas must be carefully evaluated, i.e., the identification of the critical features of the product and the identification of suit able machines to perform the required machining operations. The main aim of the project is the development of a model based on the evaluation of those two areas for identifying the critical parameters that have a direct effect on resource allocation at GKN Aerospace. Methodology - A triangulation of methods was used. A literature review was con ducted to get an overview of the research area. Quantitative and qualitative data were retrieved from GKN Aerospace and analyzed to comprehensively investigate the area of study. Findings - The products and machines of interest were assessed for identifying the critical parameters that have a direct impact on resource allocation. These results were then used to analyze the associations between product features and machine capabilities to develop a model that can help in implementing effective resource al location strategies at GKN Aerospace. Specifically, two products and about forty machines were used to test the model. Recommendations were also provided on how to improve and make the implementation of the association model more effective and responsive. Limitations - The research was limited to only the machines capable of performing certain cutting operations (turning, milling and drilling) and to only three products. The project does not include any software development to automate the association procedure between product features and machine capabilities. Moreover, due to the inaccuracy of some data (which in some cases were generalized for the purpose of running the model), the results of the association matrices may not be accurate. Furthermore, due to time constraints and lack of data, the model could only be tested for two of the three products studied.
Keywords: resource allocation, production system, product features, machine capabilities; aerospace, standardization, geometry assurance, statistical quality control, sustainability.